Accurate Design Method of the Skiving Tool for the Orthogonal Spur Face Gear - Tan Yongxu; Peng Xianlong (Jixie chuandong)
In order to improve the machining accuracy of the orthogonal spur face gear, this study proposes a precise design method of a skiving tool for the orthogonal spur face gear. Based on the meshing principle of the gear cross axis, the skiving process of the face gear is analyzed. By the involute tooth profile of the cylindrical gear meshing with the face gear, the equation of the skiving tool tooth surface is enveloped. Based on the normal section, the error-free skiving tool structure is designed and the expression of the cutters' cutting edge is deduced. Solve the meshing condition of the cutting edge and the face gear, deduce the numerical control machining law, and carry out theoretical calculation and simulation machining of the face gear's tooth surface. The numerical comparison between the skiving tooth surface and the theoretical tooth surface of the face gear shows that, the theoretical tooth surface of the face gear can be obtained when the skiving tool has no error. In the Vericut simulation, the tooth surface error can be kept within 10 μm.